Kedudukan Jaminan Perlindungan Terhadap Anak Diluar Perkawinan Ditinjau dari Konsep Hak Asasi Manusia: Position the Guarantee of Protection for Children Outside Marriage in Terms of Concept Human Rights - Rahmi Anisa; Ardiansah Ardiansah; Bahrun Azmi (Universitas Medan Area, 2022)
A child is born from the result of a legal marriage between his parents. According to Article 1 paragraph (1) of Law Number 1 of 1974 it is stated that